Incorporating Patients' Preferences Into Medical Decision Making. (February 2013) - Fraenkel, Liana
Current models of care emphasize the importance of including patients' values in the decision-making process. This is particularly important for decisions for which there are few data supporting a clear strategy or treatment choice. Constructing preferences for complex decisions requires that patients be able to consider multiple trade-offs between specific risks and benefits. Several marketing research techniques have been recently applied to heath care settings to facilitate this process. Most can be programmed to generate patients' preferences or priorities, which can then be used to improve patient–physician communication. In this article, we will describe some of the currently available approaches that have been successfully used in the health care setting. We provide case examples to illustrate the potential value of adopting each of these approaches in clinical practice.